3D computational fluid dynamics study of a drying process in a can making industry. (25th October 2016) - Tanthadiloke, Surasit; Chankerd, Warunee; Suwatthikul, Ajaree; Lipikanjanakul, Patsarawan; Mujtaba, Iqbal M.; Kittisupakorn, Paisan
Highlights: A thermal drying oven in a can making industry is simulated via a 3D CFD model. Effects of air flow rate in the oven on air velocity patterns. Effects of air flow rate in the oven on air temperature. Effects of air flow rate in the oven on food-grade lacquer concentration. This study would lead to the saving of energy consumption in the oven. Abstract: In the drying process of a can making industry, the drying efficiency of a thermal drying oven can be improved by adjusting the volumetric air flow rate of the blower. To maximize drying efficiency, an optimal flow rate is needed. Consequently, a three-dimensional computational fluid dynamics (CFD) is used to provide simulation according to the response of air velocity, air temperature and evaporated solvent concentration with respect to changes in volumetric air flow rate in the drying oven. An experimental study has been carried out to determine the evaporation rate of the solvent. To validate the models, the process data obtained from the CFD is compared with that obtained from actual data. In the accurate models, the simulation results demonstrate that the decrease in volumetric air flow rate provides no major discrepancy of the air velocity patterns in all dimensions and decreases the maximum temperature in the oven. Consequently, this decrease in volumetric air flow rate rapidly increases the evaporated solvent concentration in the beginning and then gradually decreases over the length of the oven. In addition, further reduction of the flow rate gives lower heat loss of the oven up to 83.67%.